The Effect of Risk Perception and Online Trust on Purchase Intention in E-Commerce - Ikhlash, Muhamammad; Linda, Khori Rahma (International Review of Management and Marketing, 2024)
Research on the factors influencing online trust in e-commerce has been limited in recent years. Therefore, this study is a rigorous investigation that aims to first understand the main factors that affect online trust and, second, to find out the impact of online trust on risk perception, attitude, and purchase intention. The study applies a quantitative approach method and collects primary data by filling out questionnaires from 100 respondents who have experience shopping through e-commerce applications. The sampling technique uses the purposive sampling method, ensuring a representative sample. Data collection was carried out by distributing questionnaires, and then the data was processed using SmartPLS version 4.0 to test instruments and hypotheses. The findings of this study, based on a robust methodology, show that perceived size has a significant positive effect on online trust, perceived reputation has a significant positive effect on online trust, online trust has a significant positive effect on risk perception, online trust has a significant positive effect on attitude, Risk perception has a significant positive effect on attitude, risk perception does not affect purchase intention, attitude has a significant positive effect on purchase intention, and online trust does not affect purchase intention.